Indonesian Jurisprudence Ahmad Qodri Azizy’s Perspective - Muhammad Shohibul Itmam (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2019)
This paper explains the thoughts of Indonesian jurisprudence from Ahmad Qadri Azizy's perspective. This study's focus includes, first, how is the epistemological thought of A. Qodri Azizy about Indonesian Jurisprudence, and second, how is the Indonesian Jurisprudence on A. Qodri Azizy's perspective. The method of this study is descriptive-analytical critical with normative legal approaches. The study's findings are, first, the epistemology used by A. Qodri Azizy is the integration between the common law and the Islamic law with a democratic and scientific approach known as a legal eclecticism in Indonesia. Simultaneously, the Indonesian legal science concept that the jurist designed is the effort to implement Islamic law in Indonesia. The effort to implement the Islamic law was carried out scientifically, academically, with democratization following the pluralist legal system in Indonesia.Tulisan ini menjelaskan pemikiran ilmu hukum Indonesia perspektif Ahmad Qodri Azizy. Fokus kajiannya meliputi, pertama bagaimana epistemologi pemikiran A. Qodri Azizy tentang ilmu hukum Indonesia Indonesian Jurisprudence, dan kedua, bagaimana konsep ilmu hukum Indonesia Indonesian Jurisprudence perspektif A. Qodri Azizy. Metodologi penulisan bersifat deskriptif analitis kritis dengan pendekatan hukum normatif. Temuan tulisan adalah, pertama, epistemologi yang digunakan A. Qodri Azizy adalah integrasi antara ilmu hukum umum dan ilmu hukum Islam dengan pendekatan demokrasi dan keilmuan yang dikenal dengan eklektisisme hukum di Indonesia. Sedangkan konsep ilmu hukum Indonesia yang dirancang adalah upaya posistivisasi hukum Islam di Indonesia. Upaya postivisasi dilakukan secara keilmuan, akademik dengan proses demokratisasi sesuai sistem hukum pluralis yang ada di Indonesia.